Incidence and outcomes of intracerebral haemorrhage with mechanical compression hydrocephalus. Issue 3 (8th January 2021) - Owen, Bryce; Akbik, Omar; Torbey, Michel; Davis, Herbert; Carlson, Andrew P
Abstract : Introduction: Intracerebral haemorrhage (ICH) within deep structures adjacent to the third ventricle is associated with worse outcomes when compared with lobar ICH due to the critical role of deep nuclei in normal neurological functioning. New evidence suggests another contributing factor to poor outcome is obstruction of cerebrospinal fluid outflow by clot burden causing mechanical compression of the third ventricle. The authors reviewed the incidence and outcomes of mechanical compression ICH in order to identify this high-risk group which may potentially benefit from minimally invasive evacuation. Methods: Patients with spontaneous, non-traumatic, supratentorial ICH were identified retrospectively over a 30-month period. CT imaging was reviewed to assess location of the ICH, volume of the ICH, presence of hydrocephalus requiring external ventricular drain (EVD) placement, and time to clearing of the third ventricle. Hydrocephalus was then categorised as due to 'primarily intraventricular haemorrhage (IVH)', 'primarily mechanical compression' or 'mixed'. Functional outcomes at discharge were assessed using the modified Rankin Score (mRS). Results: 287 patients met inclusion criteria, of which 39 (13.5%) patients developed hydrocephalus that required EVD. EVD patients had significantly higher mRS at discharge (p≤0.001) when compared with the non-EVD group. Lobar location was associated with lower odds of poor outcome compared with thalamic location (OR 0.107–0.560). Mechanical compression hydrocephalus was associated with poor outcome when compared with the primary IVH hydrocephalus subgroup (p=0.037) as well as longer time to clearing of the third ventricle (p=0.006). Conclusions: Mechanical obstruction requiring EVD occurs in approximately (21/287) 7.3% of all patients with spontaneous supratentorial ICH. It is unknown if the worse morbidity in these subjects is purely related to damage to deep structures surrounding the third ventricle or if secondary damage from hydrocephalus could be mitigated with targeted minimally invasive clot evacuation.